A study of clinical pathological lesions and different modalities of treatment for diabetic foot - Khedkar, Indira; Saparia, Naresh (International Surgery Journal, 2017)
Background: Diabetes Mellitus is a heterogeneous primary disorder of carbohydrate metabolism characterized by chronic state of hyperglycaemia with multi-etiological factors that generally involve absolute or relative insulin deficiency or both. Diabetic foot is defined as the foot of diabetic patients with ulceration, infection and/or destruction of the deep tissues, associated with neurological abnormalities and various degrees of peripheral vascular disease in the lower limb. So, the aim of the study was to evaluate the role of various surgical interventions like debridement, minor/major amputations in the management of diabetic foot. Methods: We have included the study of total 60 patients with foot lesion. Patients with Diabetes mellitus with lesions of foot i.e. ulcer, blister. cellulites, abscess and gangrene, presenting to the department of Surgery were treated by different types of treatment. Data analysis was done by appropriate statistical tests (descriptive analysis, chi-square test). Results: 13.33% patients underwent toe amputation, 8.88% patients had below knee amputation, 33.33% patients had debridement followed by dressing, 31.12% patients had skin grafting and 13.33% patients had incision and drainage. Conclusions: This underlines the importance of patient education regarding prophylactic foot care. Patient mortality and morbidity can be reduced by prophylactic foot care, sugar control, proper surgical treatment, regular follow-up of high risk patient, suitable administration of antibiotics.